Pengaruh Self Efficacy Dan Work Environment Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Mediasi - Akhmad Nizam Zuhri Khafidz; M. Sulhan (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study aims to determine the influence between the variables studied. These variables include self-efficacy, work environment, job satisfaction and employee performance. This type of research is associative research with a quantitative approach, the data collection technique used is a questionnaire which is distributed online using Google Forms. The sample in this research is production employees of PT. The Clod Indonesia as many as 158 respondents with a random sampling technique. The analysis technique used is Path analysis and by using the SPSS 22 application. The results show that self-efficacy has a positive and significant effect on job satisfaction with a probability value of 0.000. Work environment has a positive and significant effect on job satisfaction with a probability value of 0.000. Self efficacy has a positive and significant effect on employee performance with a probability value of 0.007. The work environment has a positive and significant effect on employee performance with a probability value of 0.036. Job satisfaction has a positive and significant effect on employee performance with a probability value of 0.000. Job satisfaction can mediate the relationship between self-efficacy and employee performance with a probability value of 0.000. Job satisfaction can mediate the relationship between work environment and employee performance with a probability value of 0.000.